Effects of Konjac (Amorphophallus muelleri Blume) Flour Addition and Drying Time on the Crude Fiber and Texture Level of Instant Yellow Rice - Anam, Choiroel; Zulfa, Fitriyah; Suleman, Dininurilmi Putri; Abdi, Yenny Febriana Ramadhan; Mulyani, Rizka; Rochmah, Alfi Nur; Adi, Prakoso; Rahmawati, Adinda Dwi (agriTECH, 2024)
Instant yellow rice is a traditional breakfast dish prepared using special technology for quick and practical cooking and a longer shelf life. Since rice has low crude fiber content as the main ingredient, substitution with local sources, such as konjac flour, can be made. Konjac flour is the powdered root of konjac plant, and it contains high crude fiber. Therefore, this study aimed to examine the texture and crude fiber properties of instant yellow rice with the addition of konjac flour. Furthermore, a completely randomized design (CRD) was used with two factors, namely variations in konjac flour concentration (2%, 3%, and 4%) and variations in drying time (5 hours, 6 hours, and 7 hours). Each sample was analyzed for the physical (hardness, stickiness and chewiness texture) and chemical characteristics (crude fiber content). The results showed that the konjac flour concentration had a significant (p<0.05) effect, while the drying time had no significant (p<0.05) effect on the physical and chemical characteristics of instant yellow rice. Therefore, 5 hours of drying might be enough for the rice processing. The addition of 2% konjac flour on instant yellow rice dried for 5 hours showed 2.48±0.50 a N of hardness texture, 5.53±0.07 c N stickiness texture, 4.59±0.02 a N chewiness texture, and 5.20% of crude fiber. Addition of 3% konjac flour on instant yellow rice dried for 5 hours showed 5.74±0.08 b N of hardness texture, 4.73±0.17 b N stickiness texture, 4.37±0.05 a N chewiness texture, and 5.20% of crude fiber. The addition of 4% konjac flour on instant yellow rice dried for 5 hours showed 6.41±0,02 c N of hardness texture, 4.06±0.70 b N stickiness texture, 3.33±1.52 a N chewiness texture, and 5.35% crude fiber. This showed the best treatment was the use of instant yellow rice with 4% konjac flour addition at 5 hours drying time.